1999
DOI: 10.1577/1548-8675(1999)019<1089:eomhoe>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mechanical Harvesting of Eurasian Watermilfoil on Largemouth Bass and Bluegill Populations in Fish Lake, Wisconsin

Abstract: We examined changes in populations of largemouth bass Micropterus salmoides and bluegill Lepomis macrochirus associated with mechanical plant harvesting in a lake heavily infested with Eurasian watermilfoil Myriophyllum spicatum. In Aug 1994, 18% of the total plant biomass in Fish Lake, Dane County, Wisconsin, was removed in a radial pattern of 2‐m‐wide channels. Largemouth bass and bluegill abundance, survival, growth, and length frequency were compared between pretreatment (1992–1993) and posttreatment (1995… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…Therefore, bluegill in reservoirs with high per cent littoral volume may experience lower growth rates as a result of increased foraging in this habitat. This finding is consistent with Unmuth et al (1999) who found increased bluegill growth rates after manual vegetation removal. Bluegill typically avoid habitats with pH ≥ 9·5 (Serafy & Harrell, 1993) but are tolerant of habitats with pH as low as 5·0 (Rahel, 1984).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, bluegill in reservoirs with high per cent littoral volume may experience lower growth rates as a result of increased foraging in this habitat. This finding is consistent with Unmuth et al (1999) who found increased bluegill growth rates after manual vegetation removal. Bluegill typically avoid habitats with pH ≥ 9·5 (Serafy & Harrell, 1993) but are tolerant of habitats with pH as low as 5·0 (Rahel, 1984).…”
Section: Discussionsupporting
confidence: 91%
“…These models include some variables that managers can attempt to manipulate to enhance growth. For example, managers can manipulate prey populations (Noble, 1981) or alter the per cent of littoral area (Unmuth et al , 1999). Other variables, however, may not be easily manipulated ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This decline in feeding efficiency has resulted in decreased growth and condition of largemouth bass in heavily vegetated systems (Colle & Shireman, 1980;Hayse & Wissing, 1996;Miranda & Pugh, 1997;Cailteux et al, 1998). When SAV is reduced, largemouth bass growth and condition increase, presumably because they have improved access to prey (Bettoli et al, 1992;Wrenn et al, 1996;Pothoven et al, 1999;Unmuth et al, 1999). Declines in SAV can result in a diet shift to prey with greater energy densities, which also leads to higher growth (Bettoli et al, 1992;Miranda & Pugh, 1997;Cailteux et al, 1998;Unmuth et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…When SAV is reduced, largemouth bass growth and condition increase, presumably because they have improved access to prey (Bettoli et al, 1992;Wrenn et al, 1996;Pothoven et al, 1999;Unmuth et al, 1999). Declines in SAV can result in a diet shift to prey with greater energy densities, which also leads to higher growth (Bettoli et al, 1992;Miranda & Pugh, 1997;Cailteux et al, 1998;Unmuth et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation